2017
DOI: 10.1136/bcr-2017-220598
|View full text |Cite
|
Sign up to set email alerts
|

Delayed progression of bull’s eye maculopathy

Abstract: Chloroquine-induced maculopathy may progress years after drug cessation and an apparent period of visual stability. Both doctor and patients should be fully aware of the risks of retinal toxicity, including delayed onset and progression. It is therefore crucial that regular monitoring continues in affected patients, long after the initial diagnosis of maculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In this 1-year follow-up, a slight increase of the atrophic area was found for patients with BEM even after cessation of drug intake, suggestive for disease progression, and in line with previous reports. 41 44 A possible reason could be the long half-life period of CQ/HCQ metabolites in retinal tissue. 45 …”
Section: Discussionmentioning
confidence: 99%
“…In this 1-year follow-up, a slight increase of the atrophic area was found for patients with BEM even after cessation of drug intake, suggestive for disease progression, and in line with previous reports. 41 44 A possible reason could be the long half-life period of CQ/HCQ metabolites in retinal tissue. 45 …”
Section: Discussionmentioning
confidence: 99%
“…Five of these patients exceeded a cumulative dose of 1000 g, as they surpassed a duration of 5 years. Sudden deterioration of vision and development of bull’s eye maculopathy were reported in patients who received a maintenance dose as low as 200 mg for more than ten years [ 19 , 20 ], as well in cases with shorter duration of use [ 21 , 22 , 23 ]. In this study, one patient with SS reported retinal toxicity within three years of the therapy but received a high dose of HCQ.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment for HCQ toxicity involves cessation of the drug and monitoring for further progression of retinal damage. The prognosis for patients with bull’s eye maculopathy due to HCQ toxicity is variable, with some patients experiencing improvement in visual function after cessation of the drug, while others may experience permanent vision loss[ 20 - 22 ]. In some cases, the damage caused by the drug may be delayed and irreversible, resulting in permanent vision loss.…”
Section: To the Editormentioning
confidence: 99%
“…In some cases, the damage caused by the drug may be delayed and irreversible, resulting in permanent vision loss. There are currently no Food and Drug Administration-approved treatments for bull’s eye maculopathy due to HCQ toxicity[ 22 ].…”
Section: To the Editormentioning
confidence: 99%